Cardiopulmonary Exercise Testing and Prognosis in Hypertrophic Cardiomyopathy. (November 2015) - Coats, Caroline J.; Rantell, Khadija; Bartnik, Aleksandra; Patel, Amour; Mist, Bryan; McKenna, William J.; Elliott, Perry M.
Abstract : Background—: Exercise testing is performed in patients with hypertrophic cardiomyopathy to evaluate blood pressure response, a risk factor for sudden cardiac death. The prognostic role of exercise gas exchange variables is unknown. Methods and Results—: Between 1998 and 2010, 1898 patients (age 47±15 years, range 16–86 years; 67% male) with hypertrophic cardiomyopathy underwent cardiopulmonary exercise testing. A total of 178 (9.4%) patients reached the primary end point of all-cause mortality or heart transplant (death/transplant) during a median follow-up of 5.6 years (interquartile range 2.6–8.9), giving an annual event rate of 1.6% per person year. Peak oxygen consumption (adjusted hazard ratio [HR] 0.82, 95% confidence interval [CI] 0.77–0.88, P <0.001), ventilatory efficiency (adjusted HR 1.10, 95% CI 1.00–1.22, P =0.049), and ventilatory anaerobic threshold (adjusted HR 0.82, 95% CI 0.70–0.96, P =0.016) were predictors of the primary outcome after correction for age, sex, left atrial size, nonsustained ventricular tachycardia, and ejection fraction. The overall adjusted death/transplant estimates for patients in the lowest quartile with peak oxygen consumption ⩽15.3 mL/kg/min were 14% at 5 years and 31% at 10 years. Peak oxygen consumption (HR 0.81, 95% CI 0.77–0.86, P <0.01) and ventilation to carbon dioxide production (HR 1.10, 95% CI 1.08–1.13, P <0.001) were predictors of death because of heart failure or transplantation but not sudden cardiac death or implantable cardioverter defibrillator shocks. Conclusions—: Cardiopulmonary exercise testing provides prognostic information in patients with hypertrophic cardiomyopathy. Submaximal exercise parameters, such as ventilatory efficiency and anaerobic threshold, measured alone or in combination with peak oxygen consumption, predict death from heart failure.